ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL MATERI FUNGSI DAN RELASI - Riayanti Agustin; Redo Martila Ruli (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Analysis of students' difficulties aims to assist teachers in analyzing difficulties in solving material relationships and functions. The research method used is phenomenologically qualitative in junior high school in one of the schools in Karawang district in the odd semester of the 2022/2023 academic year. Sampling was 41 students of class VIIIB. In this study, this collection technique took data with test results based on the number of questions as many as 3 questions and what was used was tests and interviews, based on the results of analysis and discussion and observation. The validity of the data used in this study is a type of source triangulation. The results of this study indicate that students who experience difficulties in solving material relations and function questions are: (1) junior high school students who have difficulty using concepts because students cannot translate the form of the questions, so they cannot use the appropriate formula. (2) ) junior high school students have difficulty using principles because students cannot process calculations, so students do not complete calculations correctly, (3) junior high school students have difficulty solving verbal problems because students cannot use concepts and principles to work on problems on questions.